Mechanistic insights derived from re-establishment of desiccation tolerance in germinating xerophytic seeds: Caragana korshinskii as an example - Peng, Long; Huang, Xu; Qi, Manyao; Pritchard, Hugh W.; Xue, Hua (Frontiers in Plant Science, 2022)
Germplasm conservation strongly depends on the desiccation tolerance (DT) of seeds. Xerophytic seeds have strong desiccation resistance, which makes them excellent models to study DT. Although some experimental strategies have been applied previously, most methods are difficult to apply to xerophytic seeds. In this review, we attempted to synthesize current strategies for the study of seed DT and provide an in-depth look at Caragana korshinskii as an example. First, we analyze congenital advantages of xerophytes in the study of seed DT. Second, we summarize several strategies used to study DT and illustrate a suitable strategy for xerophytic species. Then, based on our previous studies work with C. korshinskii, a feasible technical strategy for DT re-establishment is provided and we provide illustrate some special molecular mechanisms seen in xerophytic seeds. Finally, several steps to unveil the DT mechanism of xerophytic seeds are suggested, and three scientific questions that the field should consider are listed. We hope to optimize and utilize this strategy for more xerophytic species to more systematically decipher the physiological and molecular processes of seed DT and provide more candidate genes for molecular breeding.